FACTOR ANALYSIS OF COAL MINING INDUSTRY IN AIR SEBAYUR VILLAGE - Dewanti, Diah Setyawati; Novitasari, Rizki (Universitas Muhammadiyah Yogyakarta, 2019)
This research aims to analyze the economic impact of environment to Air Sebayur communities on coal mining industry. This paper is use primary data, consist of 100 respondents as the communities of Air Sebayur village, who lived in the edge of the road to coal mining industry. The data collection applied the non-probability sampling methods which is purposive sampling based on the location of the house. Factor analysis applied as to achieve the aim of this research. Through factor analysis, this paper could define the economic impacts on the environment caused by the mining coal activities. This paper discovers two (2) main factors which formed by 5 significant variables. The main factors are environments factors and health factors. Environments factors consists of variables on compensating cost by the dust, frequency of sweeping the floor and the frequency of sweeping on balcony. Health factors define into variables of health cost and the type of illness of communities who lived in the edge of the road to coal mining industry.